Incremental diagnostic value of CMR-derived LA strain and strain rate in dialysis patients with HFpEF. Issue 151 (June 2022) - Zhou, Hang; An, Dong-Aolei; Ni, Zhaohui; Xu, Jianrong; Zhou, Yan; Fang, Wei; Lu, Renhua; Ying, Liang; Huang, Jiaying; Yao, Qiuying; Li, Dawei; Hu, Jiani; et al.
Abstract: Objectives: To test whether left atrial (LA) strain and strain rate add incremental value in the diagnosis of heart failure with preserved ejection fraction (HFpEF) in dialysis patients over clinical and conventional parameters only. Background: HFpEF frequently occurs in dialysis patients, however, the diagnosis of HFpEF is difficult. Although HFpEF is always companied with LA dysfunction, the performance of novel LA parameters, LA strain, and strain rate, in the diagnosis of HFpEF among dialysis patients remains unknown. Methods: In the study, 153 dialysis patients (57 without HFpEF and 96 with HFpEF) and 52 healthy controls underwent cardiovascular magnetic imaging (CMR). Three components of LA strain and strain rate, including reservoir, contractile, and booster pump, were assessed via the CMR feature tracking module. Extra diagnostic value was examined by Harrell's C-statistic. Results: Compared with healthy controls and dialysis patients without HFpEF, dialysis patients with HFpEF had significantly impaired LA reservoir (εs) and contractile (εe) strain and strain rate (SRs, SRe), all p < 0.0001. Among these parameters, εs, εe, and SRe showed relatively high accuracy in diagnosing HFpEF among dialysis patients (areas under the curve: 0.84, 0.91, and 0.90, respectively). Reduction of εs, εe, and SRs provided incremental diagnostic value over conventional clinical and echocardiogram parameters. Combined with εs, εe or SRs, the diagnostic performance was further improved (Harrell's C-statistic: 0.83 vs. 0.96, 0.97, and 0.97, respectively, all p < 0.0001). Conclusions: CMR-derived εs, εe, and SRs might add incremental diagnostic value over conventional indexes in diagnosing HFpEF among dialysis patients.